Phylogenetic and divergence time analysis of the Chelonoidis chilensis complex (Testudines: Testudinidae) - Sánchez, Julieta; Holley, Juan A.; Poljak, Sebastián; Bolzán, Alejandro D.; Bravi, Claudio M. (Zootaxa, 2017)
We present a phylogenetic and divergence time analysis of the Chelonoidis chilensis complex (the southernmost tortoises of South America) within crown Testudinidae. We compiled a dataset of 1118 bp cytochrome b (cyt b) sequences derived from 111 individuals sampled across the known geographic range of the species, and performed a phylogenetic analysis employing Maximum Parsimony, Maximum Likelihood and Bayesian Inference methods. The resulting trees showed similar topologies and support values. The C. chilensis complex was always recovered as a monophyletic group composed by two major clades (i.e. haplogroups). The biogeographic distribution of one of these clades overlaps with the Dry Chaco eco–region, while the biogeographic distribution of the other overlaps with the Monte eco–region. In order to date the origin and diversification time of these two clades, we employed a previously published two-step molecular clock method. In the first step we dated the time of origin of C. chilensis as a clade within the Testudinidae family using new and previously published sequences, extinct testudinid taxa for age calibration and the Fossilized Birth-Death (FBD) model. In the second step we dated the divergence between the haplogroups of C. chilensis based on the time of origin estimated in the first step and a coalescent evolution model. Our results suggest that divergence between Dry Chaco and Monte tortoises may have occurred about 2.47 million of years ago. We interpret these results in the light of the environmental and geological changes that occurred during the late Pliocene to Middle Pleistocene of South America.